A Case Report of a 3-Year-Old Child With Anaphylactic Shock After a Diclofenac Suppository Confirmed by Serial Tryptase and a Basophil Activation Test - Huang, Wun-Yan; Chiu, Tsu-Man; Kuo, Su-Feng; Chung, Wen-Hung; Tsai, Yi-Giien (Frontiers in Pediatrics, 2022)
Diclofenac is one of the most commonly used non-steroidal anti-inflammatory drug (NSAID) agents for fever management by general practitioners. Anaphylaxis due to suppository of diclofenac sodium (Voltaren) is extremely rare in children. We report the case of a 3-year-old girl with anaphylactic shock after a diclofenac suppository with confirmation by serial tryptase and a basophil activation test.